2014
DOI: 10.1124/mol.114.094029
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Organization of Ca2+ Signals That Regulate Synaptic Release Efficacy in Sympathetic Neurons

Abstract: ABSTRACTsignals operating near Ca 21 sources in the AZ are organized into discrete fast and slow temporal phases that remodel exocytosis and short-term plasticity to ensure long-term stability in acetylcholine release efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…Our approach differs from previous studies using transgenic mouse models to reduce SV2A levels, which may potentially be confounded by accompanying compensatory and/or developmental changes (Crèvecœur et al ., ). Throughout, the siRNA experiments were controlled by an appropriate nsRNA; in this regard, the nsRNA construct produced control parameters, including EPSP amplitude, RRP size, overall vesicle count and synaptic depression characteristics, which were in good agreement with control data from our previous studies in SCG neurons (Krapivinsky et al ., ; Ma et al ., ; Tanifuji et al ., ; Mori et al ., ), suggesting that the injection of RNA had no detrimental effects per se on basal cell physiology in this experimental system (Ma & Mochida, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our approach differs from previous studies using transgenic mouse models to reduce SV2A levels, which may potentially be confounded by accompanying compensatory and/or developmental changes (Crèvecœur et al ., ). Throughout, the siRNA experiments were controlled by an appropriate nsRNA; in this regard, the nsRNA construct produced control parameters, including EPSP amplitude, RRP size, overall vesicle count and synaptic depression characteristics, which were in good agreement with control data from our previous studies in SCG neurons (Krapivinsky et al ., ; Ma et al ., ; Tanifuji et al ., ; Mori et al ., ), suggesting that the injection of RNA had no detrimental effects per se on basal cell physiology in this experimental system (Ma & Mochida, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that SV2B deletion in rod bipolar cells caused a slowing in recovery of membrane capacitance in response to a train of stimuli, potentially reflecting a slowing in the rate of endocytosis (Wan et al ., ). These effects were proposed to occur secondarily to changes in Ca 2+ signaling (see also Mori et al ., ). Overall, our data support a scenario whereby, in control conditions, empty release slots are filled rapidly after the cessation of high‐frequency stimulation through vesicles from the recycling pool, whereas, under conditions of SV2A knockdown, this process takes longer and appears to be more reliant on slower endocytic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). 9 , 12 ) The SCG neuron has a large cell body and nucleus that allows for the manipulation of gene expression and protein function in mature neurons via acute microinjection of cDNA, small interfering RNA (siRNA), dominant-negative transgenes, peptides, antibodies, and/or metabolites, 9 , 13 16 ) an approach not technically feasible for cultured neurons from the central nervous system. In addition, synaptic activity and short-term plasticity, because they relate to the size and replenishment of functional SVs pools, can be accurately monitored by recording excitatory postsynaptic potentials (EPSPs) evoked by APs in presynaptic neurons.…”
Section: Introductionmentioning
confidence: 99%